Figurative language and emotional trauma when the recipient - Jaber, Yusuf; Khalil, Bassam (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The literature is a human actor presence, installation literary intensify and the embodiment of human thought creative in the extreme cognitive, sensory energies, and because the man is the object searcher for meaning and not the owner of this sense; from here we can not understand the human being away from the literat6ure, and we can not understand the human self away from broker literature, enriched by the language of sound and the relationship of the code and text. - We have tried in this research to approach the nature of the relationship between language and human self, and to recognize the ability of the word to influence with receiver, but publicly we were able to monitor the movements of the word, and keep up with changing capacity if it is a single or in a composition and then rouse the capacity to incite emotion of reader , emotionally and intellectually tomoves the word from the carrier for the event to view the role of the industry and moving the human conscious crowd , which owns the logical of mental functioning .